1965
DOI: 10.1037/h0022705
|View full text |Cite
|
Sign up to set email alerts
|

Birth order and academic primogeniture.

Abstract: STAR, K. An experimental study of "reactive inhibition" and its relation to certain personality traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
3
5

Year Published

1968
1968
1985
1985

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 9 publications
2
13
3
5
Order By: Relevance
“…3) Altus (1965) are about twice as large as the percentages found in the present study, particularly in the case of male Ss. Thus, while Altus found that over 60% of the entering students are firstborn if the only child is included, the corresponding figure reported in this study is only 33%.…”
contrasting
confidence: 36%
See 2 more Smart Citations
“…3) Altus (1965) are about twice as large as the percentages found in the present study, particularly in the case of male Ss. Thus, while Altus found that over 60% of the entering students are firstborn if the only child is included, the corresponding figure reported in this study is only 33%.…”
contrasting
confidence: 36%
“…However, while Alms ( 1965) reported that over 90% of his sample came from families of 1 through 4 children, Table 2 shows that only 48% of our Sample come from families of 1 through 4. The finding by Altus ( 1965) that small families are better represented in college than are large families may be a reflection of the greater preponderance of small families in the American society at large rather than, as Alms ( 1965) concluded, an indication of a close association between college attendance and family size. Similarly, the present findings may be a reflection of the typically large Arab family characteristic of the Middle East society.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Both the data recorded by Altus (1965a) and data recorded by Schachter (1963) During that period, the percent of first borns ranged from 52.5% between 1951-54 and a high of 66% in the period petween 1955-58 (Schachter, 1963).…”
Section: Educational Attainmentmentioning
confidence: 99%
“…Between 1960, Altus (1965a collected data on all incOming students from one-, two-, three-and four-child families at the University of California at Santa Barbara. He found that the percentages of first borns from the two-, three-, and four-child families were respectively 63.0, 50.5, 50.5%.…”
Section: Educational Attainmentmentioning
confidence: 99%